Superoxide-mediated O2 activation drives radical cyclization in ergot alkaloid biosynthesis - Yuanyuan Jiang; Zhong Li; Shengying Li (Engineering Microbiology, 2025)
Conventional heme enzymes utilize iron–oxygen intermediates to activate substrates and drive reactions. Recently, Chen et al. discovered a novel NADPH-independent superoxide mechanism of heme catalase EasC, which facilitates an O2-dependent radical oxidative cyclization reaction during ergot alkaloid biosynthesis. This enzyme coordinates superoxide-mediated catalysis by connecting spatially distinct NADPH-binding pocket and heme pocket via a slender tunnel, offering a novel perspective on the catalytic mechanisms of heme enzymes in nature.